(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article highlights the role of culture in developing modern approaches and strategic foundations for promoting a healthy lifestyle in the pedagogical education system. It discusses current changes in the field of physical education and sports, as well as issues related to engaging student youth in a healthy lifestyle.